IPTEKS OM-SPAN PADA DIREKTORAT JENDERAL PERBENDAHARAAN NEGARA SULAWESI UTARA - Assa, Jeremia Renaldo; Warongan, Jessy (Universitas Sam Ratulangi, 2018)
This report shows how modernization greatly influences the performance carried out, which makes work easier and faster precisely. using the online monitoring application SPAN on the performance of employees at the directorate general of the state of North Sulawesi, especially in the internal part of the company to be more efficient in monitoring stakeholders. this report is compiled descriptively and qualitative data collection. the results of which affect work, resulting in satisfactory work results in the directorate general of the state treasury of North Sulawesi.Keywords : modernization, online monitoring, SPANÂ